Perbandingan Kenaikan Berat Badan Bayi yang Dilakukan Pijat Bayi dan Tidak di RW 06 Dan 07 Kampung Tutugan Desa Cihanjuang Rahayu Kecamatan Parongpong Kabupaten Bandung Barat - Erni Hernawati (STIKes Karsa Husada Garut, 2015)
Infant massage is therapeutic touch of the oldest and most popular known to people. Stimulus or stimuli given earlier can also tighten the love of parents with children and healthy bond. Infant massage done by the parents themselves can increase milk production and weight gain in infants, but today there are many parents who do not understand about baby massage example is they always massaging the baby while the baby is in a state of pain while massaging requirement is the baby must in a healthy state. The purpose of research to determine the ratio of weight gain in infants who do baby massage and not in the village of Kampung Tutugan Cihanjuang Rahayu. This study uses a comparative research design is the design of the experiment with ways to intervene in some groups, the population in this study were all infants aged 3-7 months in Rw 06 and 07 village Tutugan in May 2013 as many as 68 babies, sampling techniques using total sampling. Babies will be massaged for 30 days and will be weighed twice, namely the initial weight before weighing and weight after 30 days do baby massage, data analysis using T test results showed that there were differences significant weight gain in infants which do massage and not to the value of P value <0.000.